A Highly Sensitive Cell-Based TLR Reporter Platform for the Specific Detection of Bacterial TLR Ligands - Radakovics, Katharina; Battin, Claire; Leitner, Judith; Geiselhart, Sabine; Paster, Wolfgang; Stöckl, Johannes; Hoffmann-Sommergruber, Karin; Steinberger, Peter (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) are primary pattern recognition receptors (PRRs), which recognize conserved microbial components. They play important roles in innate immunity but also in the initiation of adaptive immune responses. Impurities containing TLR ligands are a frequent problem in research but also for the production of therapeutics since TLR ligands can exert strong immunomodulatory properties even in minute amounts. Consequently, there is a need for sensitive tools to detect TLR ligands with high sensitivity and specificity. Here we describe the development of a platform based on a highly sensitive NF-κB::eGFP reporter Jurkat JE6-1 T cell line for the detection of TLR ligands. Ectopic expression of TLRs and their coreceptors and CRISPR/Cas9-mediated deletion of endogenously expressed TLRs was deployed to generate reporter cell lines selectively expressing functional human TLR2/1, TLR2/6, TLR4 or TLR5 complexes. Using well-defined agonists for the respective TLR complexes we could demonstrate high specificity and sensitivity of the individual reporter lines. The limit of detection for LPS was below 1 pg/mL and ligands for TLR2/1 (Pam3CSK4), TLR2/6 (Fsl-1) and TLR5 (flagellin) were detected at concentrations as low as 1.5 ng/mL, 0.2 ng/mL and 10 pg/mL, respectively. We found that the JE6-1 TLR reporter cells have the utility to characterize different commercially available TLR ligands as well as more complex samples like bacterially expressed proteins or allergen extracts. Impurities in preparations of microbial compounds as well as the lack of specificity of detection systems can lead to erroneous results and currently there is no consensus regarding the involvement of TLRs in the recognition of several molecules with proposed immunostimulatory functions. This reporter system represents a highly suitable tool for the definition of structural requirements for agonists of distinct TLR complexes.